A rare large cutaneous chondroid syringoma involving a toe: A case report. Issue 5 (February 2018) - Lu, Hui; Chen, Li-Feng; Chen, Qiang; Shen, Hui; Liu, Zhenfeng
Abstract: Rationale: Chondroid syringoma (CS) occurs mostly on the face and neck, and rarely occurs in the toe. Malignant CS is invasive, grows quickly, and has a high recurrence rate. The presence of a bilobed CS in 1 toe has never been reported in the literature. Patient concerns: A 72-year-old male patient presented with a mass in a third toe of his right foot. The mass had slowly grown in 2 years. He felt mild pain and the mass occupied most of the tip of the toe. Diagnoses: Radiographs showed a large soft-tissue mass in the third toe of his right foot without any bone destruction. Ultrasonogram showed 2 partly fused hypoechoic masses within the lesion. The mass was therefore diagnosed as a benign CS. Interventions: We amputated the toe with the mass under local anesthesia. The postoperative pathohistological examinations confirmed that the lesion was a bipartite CS exhibiting active cellular proliferation. Outcomes: Two years after surgery, there was no tumor recurrence. Lessons: CS can also present as multiple adjacent masses. Complete surgical resection and long-term follow-up are essential.